2. Uluslararası Prof. Dr. Fuat Sezgin İslâm Bilim Tarihi Sempozyumu Bildiriler Kitabı - Kaya, Mehmet Cuneyt; Ozdemir, Nihal; Aksoy, Gursel (Istanbul University Press, 2023)
In order to preserve the memory of the late Prof. Dr. Fuat Sezgin (d. 2018) and to ensure that his significant scientific legacy serves as a source of inspiration for future generations, the 1st International Prof. Dr. Fuat Sezgin Symposioum on the History of Science in Islam, in collaboration with Istanbul University, Fatih Sultan Mehmet Foundation University, and the Prof. Dr. Fuat Sezgin Research Foundation for the History of Science in Islam held its inaugural conference between June 13-15, 2019. Subsequently, IU Press published 38 of the papers that had been presented at the conference. Following this, the decision was made to organize the symposium every two years, and preparations were undertaken for the 2nd International Prof. Dr. Fuat Sezgin Symposium on the History of Science in Islam, which was held on October 7-9, 2021 with the theme of "Methodological Approaches to the History of Science in Islam." The study of the intellectual output from the Islamic world as an object of research has a nearly 200-year history. Despite the efforts of many international scholars to discover, understand, and interpret the history of Islamic sciences and determine its relevance for contemporary society, many aspects of the history of Islamic sciences still exist that remain to be clarified, such as the individuals, works, theories, networks of relations, contexts, and influences. Two key questions facing researchers in this field is how to approach the history of Islamic sciences using methodological tools and how to utilize perspectives from different disciplines. The 2nd International Prof. Dr. Fuat Sezgin Symposium on the History of Science in Islam aimed to address these issues by discussing the methodological aspects of how to research the history of Islamic sciences with a focus on the following questions: • How does the study of the history of Islamic sciences relate to the established historiography and research methods? • How can the history of Islamic sciences be periodized? Is creating a periodization that encompasses all sciences possible, or should separate periodizations be established for each individual science? • Can special methods be mentioned for studying the period following the 13th century that is commonly referred to as the post-classical period? • Has the paradigm of decline in understanding the history of Islamic sciences truly expired? • What opportunities and weaknesses do content-oriented and context-oriented approaches have in regard to analyzing scientific texts? • How should the relationship Islamic sciences have with the scientific accumulation of other civilization basins be handled? • What kind of balance should be established between continuity and originality when writing the history of scientific theories? • To what extent is the perspective presented by global history studies functional in understanding the history of Islamic sciences? • What kinds of methods and approaches should be used in teaching the history of general science at different levels, including the history of Islamic sciences? A total of 68 scholars, 41 from Turkey and 27 from other countries such as Germany, the United States of America, Belgium, France, the Netherlands, Iran, Spain, Switzerland, Egypt, Uzbekistan, Syria, Tunisia, and Greece participated in 16 parallel sessions. The symposium was conducted in a hybrid format to take into account the ongoing pandemic, with 51 of the presenters having attended the symposium in person and 17 having presented their papers online. The symposium was also broadcast live on the internet ((https://www.youtube.com/watch?v=Q11sAL3l5CI&t=8s and https://www. youtube. com/watch?v=jyrnK3q4Loc). This collection of papers offers readers 30 of the papers that were presented at the symposium and has been organized into five main sections: Methodological Approaches to the History of Science in Islam; Mathematical Sciences; Medicine; Natural Sciences; and Geography, Cartography, and Linguistics.